The general form of the equation of a circle is:
(x - h)2 + (y - k)2 = r2
Where, (h, k) is the centre of the circle.
r is the radius of the circle.
Substituting the centre and radius of the circle in he general form:
⇒ (x - a)2 + (y - a)2 = (√2)2
⇒ (x - a)2 + (y - a)2 = 2
Ans; equation of a circle with Centre (a, a) and radius
(x - a)2 + (y - a)2 = 2
Rate this question :
The equation of tRD Sharma - Mathematics
Show that tRD Sharma - Mathematics
If the circle x<sRD Sharma - Mathematics
The circle xRD Sharma - Mathematics
If the circles x<RD Sharma - Mathematics
If the centroid oRD Sharma - Mathematics